Pneumocystis jirovecii pneumonia in non-HIV patients: need for a more extended prophylaxis - Sauvat, Léo; Denis, Laure; Nourrisson, Céline; Poirier, Philippe; Ruivard, Marc; Le Guenno, Guillaume (Frontiers in Medicine, 2024)
Pneumocystis jirovecii pneumonia (PCP) has a significant mortality rate for non-HIV immunocompromised patients. Prevention is primarily based on combined trimethoprim and sulfamethoxazole (TMP-SMX) but guidelines on pneumocystosis prophylaxis are scattered and not consensual.Objectives This study aims to describe PCP in non-HIV patients and to review case by case the prior indication of prophylaxis according to specific guidelines. We included patients with confirmed diagnosis of PCP admitted to one university hospital from 2007 to 2020. Prior indication for pneumocystis prophylaxis was assessed according to the specific guidelines for the underlying pathology or treatment.Of 150 patients with a medical diagnosis of PCP, 78 were included. Four groups of underlying pathologies were identified: hematological pathologies (42%), autoimmune diseases (27%), organ transplantation (17%), and other pathologies at risk of PCP (14%). A small subgroup of 14 patients (18%) had received a prior prescription of pneumocystis prophylaxis but none at the time of the episode. Transfer to intensive care was necessary for 33 (42%) patients, and the mortality rate at 3 months was 20%. According to international disease society guidelines, 52 patients (59%) should have been on prophylaxis at the time of the pneumocystis episode. Lowest compliance with guidelines was observed in the hematological disease group for 24 patients (72%) without prescription of indicated prophylaxis. Conclusions Infectious disease specialists should draw up specific prophylactic guidelines against pneumocystis to promote a better prevention of the disease and include additional criteria in their recommendations according to individual characteristics to prevent fatal cases.